Side Trip Multipath Routing Protocol for Spatial Node Failure in Data-Gathering WSNs. (10th April 2016) - Fujita, Keisuke; Takaki, Yumi; Ohta, Chikara; Tamaki, Hisashi
In severe disaster environments, data-gathering wireless sensor networks possibly suffer from spatial node failure due to external factors such as land slide and river overflow. In order to enhance tolerance to spatial node failure, this paper proposes not only a multipath data gathering protocol called "Side Trip (ST)" scheme but also an improved version of ST scheme called "Side Trip with Network Coding (STNC)" scheme. In the ST scheme, a node establishes a secondary path which passes through nodes almost the same hop count away from the sink in order to spatially separate the path from the primary path and enhance spatial node-failure tolerance. In the STNC scheme, redundant packets from different source nodes are network-coded into an encoded packet in order to reduce the number of redundant packets and the impact on the system lifetime. We compare the ST scheme, STNC scheme, and two existing multipath protocols (i.e., H-SPREAD (Hybrid-Secure Protocol for REliable dAta Delivery) scheme and SMRP (Subbranch Multipath Routing Protocol) scheme) by means of a self-developed simulator. Simulation results show that STNC scheme and ST scheme enhance tolerance to node-failure compared to H-SPREAD scheme and SMRP scheme with no significant impact on system lifetime.